In silico study of Plasmodium 1-deoxy-dxylulose 5-phosphate reductoisomerase (DXR) for identification of novel inhibitors from SANCDB - Diallo, Bakary N'tji (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Malaria remains a major health concern with a complex parasite constantly developing resistance to the different drugs introduced to treat it, threatening the efficacy of the current ACT treatment recommended by WHO (World Health Organization). Different antimalarial compounds with different mechanisms of action are ideal as this decreases chances of resistance occurring. Inhibiting DXR and consequently the MEP pathway is a good strategy to find a new antimalarial with a novel mode of action. From literature, all the enzymes of the MEP pathway have also been shown to be indispensable for the synthesis of isoprenoids. They have been validated as drug targets and the X-ray structure of each of the enzymes has been solved. DXR is a protein which catalyses the second step of the MEP pathway. There are currently 255 DXR inhibitors in the Binding Database (accessed November 2017) generally based on the fosmidomycin structural scaffold and thus often showing poor drug likeness properties. This study aims to research new DXR inhibitors using in silico techniques. We analysed the protein sequence and built 3D models in close and open conformations for the different Plasmodium sequences. Then SANCDB compounds were screened to identify new potential DXR inhibitors with new chemical scaffolds. Finally, the identified hits were submitted to molecular dynamics studies, preceded by a parameterization of the manganese atom in the protein active site.
Keywords: Plasmodium 1-deoxy-dxylulose 5-phosphate reductoisomerase; Isoprenoids; Plasmodium; Antimalarials; Malaria -- Chemotherapy; Molecules -- Models; Molecular dynamics; South African Natural Compounds Database